"An Earnest Desire for the Truth despite Its Possible Unpleasantness": A Comparative Analysis of the Atlanta University Publications and American Journal of Sociology, 1895 to 1917. Issue 1 (January 2018) - Daniels, Kalasia Shqueen; Wright, Earl
The authors examine the methodological sophistication of the research conducted by the W.E.B. Du Bois–led Atlanta Sociological Laboratory (ASL), the first American school of sociology, and Albion Small–edited American Journal of Sociology ( AJS ). Comparative analysis of the ASL publications and scholarly articles in AJS between 1895 and 1917 is undertaken to identify articulations of the method(s) of research offered in both. The authors conclude that the articulation of research methods by the ASL is superior to those from AJS . Moreover, the authors propose that Du Bois's school was the first to institutionalize the presentation of a methods section in its research publications. Despite the ASL's contributions to the discipline, the authors argue that scientific racism, institutional racism, and the blacklisting of Du Bois because of his embrace of communism and socialism contribute to the laboratory's 100-year sociological marginalization. Ultimately, the authors propose that the ASL, in its entirety and not as an addendum to its relationship to Du Bois, be incorporated into the sociological canon as vigorously as the Chicago School.